Ze-Qi-Tang Formula Induces Granulocytic Myeloid-Derived Suppressor Cell Apoptosis via STAT3/S100A9/Bcl-2/Caspase-3 Signaling to Prolong the Survival of Mice with Orthotopic Lung Cancer - Zi-hang Xu; Yang-zhuangzhuang Zhu; Lin Su; Xue-yang Tang; Chao Yao; Xiao-ning Jiao; Yi-fei Hou; Xiao Chen; Lu-yao Wei; Wan-tao Wang; Jie Wang; Chen-yuan Gong; et al. (Hindawi Limited, 2021)
Non-small-cell lung cancer (NSCLC) remains the most common malignancy with the highest morbidity and mortality worldwide. In our previous study, we found that a classic traditional Chinese medicine (TCM) formula Ze-Qi-Tang (ZQT), which has been used in the treatment of respiratory diseases for thousands of years, could directly inhibit the growth of human NSCLC cells via the p53 signaling pathway. In this study, we explored the immunomodulatory functions of ZQT. We found that ZQT significantly prolonged the survival of orthotopic lung cancer model mice by modulating the tumor microenvironment (TME). ZQT remarkably reduced the number of MDSCs (especially G-MDSCs) and inhibited their immunosuppressive activity by inducing apoptosis in these cells via the STAT3/S100A9/Bcl-2/caspase-3 signaling pathway. When G-MDSCs were depleted, the survival promotion effect of ZQT and its inhibitory effect on lung luminescence signal disappeared in tumor-bearing mice. This is the first study to illustrate the immunomodulatory effect of ZQT in NSCLC and the underlying molecular mechanism.